Analysis of Archetypal Characters in Anita Nair’s Mistress and Lessons in Forgetting - et. al., Hema. R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper analyses the archetypal elements present in the select women characters in the novels Mistress and Lessons in Forgetting. The archetypal presence is in the form of Indian mythological characters. This presence resides in the unconscious psyche of the characters Radha and Akhila. Radha identifies herself with mythological Radha and Ahalya. Akhila identifies herself with goddess Kanyakumari. The paper also analyses how these archetypal presence make them subjugated women and also how they help them to move beyond their stereotypical roles they play in the family and society. The characters Radha and Meera are ordinary women who emerge as potential, emancipated women at a later stage. They struggle in the process of transition from tradition to modernity. In their quest for identity, they emerge as strong and independent women. The paper is analyzed from Jungian perspective of archetypes.